Associations of Multifaceted Subjective Age with Health and Well-Being in Japan - Hikari Kinjo; Markus Wettstein; Susanne Wurm (GeroPsych, 2026)
Abstract: Despite the growing attention on the significant relationship between subjective age (SA) and quality of life, it is still under debate how to conceptualize and measure SA, how to understand it within theoretical frameworks of lifespan development, and how SA relates to health and well-being, particularly in non-Western populations. This study took a multifaceted approach to explore this issue. We assessed multiple SA measures (felt age, physical age, ideal age, appearance age, interest age, and various composite measures) in a non-Western sample comprising 2,896 Japanese adults aged 20–89 to compare their associations with sociodemographic, health and well-being variables. Correlation and hierarchical regression analyses showed that better health and greater well-being were particularly closely associated with feeling physically younger. Ideal age showed opposite trends to the other single SA measures. Furthermore, ideal age was the only single index that showed a significant association with the Happiness Scale in the regression analysis, such that a stronger wish to be younger was associated with lower happiness. Discrepancy-based composite measures offered additional insight into within-person inconsistency, potentially indicating ambivalent feelings toward aging and intrapersonal incongruencies in one’s SA. This study highlights the importance of adopting a multifaceted perspective on SA to gain a broader understanding of how different SA measures are related to health and well-being in a non-Western cultural context.